Comprehensive management of high-grade knee injuries: a case report and surgical technique on patellar tendon rupture with multi ligament injury following self reduced posterior dislocation of knee - B, Rajeev P.; M., Jyothiprasanth; R., Jithin C.; Krishnan, Abhiram; Jabbar, Jithin Abdul (International Journal of Research in Orthopaedics, 2025)
Knee dislocations and patellar tendon ruptures are rare but complex injuries. Incidence of patellar tendon rupture is approximately 0.5% of the general population each year. These injuries are often present with a wide range of symptoms, depending on the structures involved. Significant soft tissue damage is almost always present, frequently accompanied by multi-ligamentous injuries and bony involvement. The potential for neurovascular compromise, particularly injury to the popliteal artery, adds to the urgency of prompt diagnosis and management and are considered as surgical emergencies. Delayed diagnosis or inadequate treatment can lead to devastating complications. A 42-year-old male presented with a high-grade knee injury diagnosed with a complete patellar tendon rupture, complete anterior cruciate ligament (ACL) disruption, and partial posterior cruciate ligament (PCL) tear, along with complex tears in both the medial, lateral menisci and osteochondral fractures, posing challenges for surgical planning. Single stage surgical intervention was planned. ACL reconstruction with peroneus longus tendon graft, medial meniscal balancing, lateral meniscal root repair and semitendinosus graft was harvested with an open stripper with insertion kept intact for patellar tendon repair with augmentation. PCL and collateral ligaments were managed conservatively since they found stable. A tailored rehabilitation protocol focused on early mobilization and progressive strengthening was implemented postoperatively. This case highlights the complexity of high-grade knee injuries involving multiple structures and the importance of thorough evaluation and surgical intervention. The tailored rehabilitation protocol facilitated recovery, leading to significant improvements in range of motion (ROM) and functionality. Individualized management strategies are crucial for addressing these complexities, ultimately enhancing patient outcomes and minimizing complications.